Strategi Komunikasi BP3MI dalam Meningkatkan Kesadaran Masyarakat tentang Hak-hak Pekerja Migran Indonesia - Beatania Jelina Ngamung; Alponia Kartini Nurhayati; Yunita Huberta Siska Henukh; Fransiskus Maurice Riberu; Lasarus Jehamat; Imelda Nahak; Helga Maria E. Gero (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Indonesian Migrant Workers constitute a labor group that makes a significant contribution to the national economy through remittances, particularly from regions with high migration intensity such as East Nusa Tenggara Province; however, the strong public interest in working abroad is often not accompanied by adequate understanding of safe migration procedures, protection mechanisms, and the rights and obligations of migrant workers. This condition has led to serious problems, including the increasing number of non-procedural migrant workers, deportation cases, and vulnerability to human trafficking crimes, indicating an information and communication gap between migrant worker protection institutions and prospective migrant workers. This study aims to analyze the communication strategies implemented by the Indonesian Migrant Workers Protection Service Center of East Nusa Tenggara Province in enhancing public awareness of migrant workers’ rights. A qualitative approach with a descriptive method was employed to provide an in-depth portrayal of the communication practices carried out by the institution, with data collected through in-depth interviews, observation of socialization activities, and documentation studies. Data analysis was conducted using the interactive model of Miles and Huberman, while the conceptual analytical framework was based on the Shannon–Weaver Two-Way Communication Model to assess message delivery effectiveness, communication channels, message recipients, and feedback mechanisms. The findings indicate that the Indonesian Migrant Workers Protection Service Center of East Nusa Tenggara Province has implemented various communication strategies, including direct community outreach, pre-departure orientation, the use of visual and audio media, and cross-sector collaboration with local governments and community leaders. Although these strategies contribute to increasing public knowledge regarding migration procedures and migrant workers’ rights, their effectiveness remains constrained by low literacy levels, challenging geographical conditions, and weak feedback mechanisms from target communities. The study concludes that strengthening dialogic and participatory communication, simplifying messages to improve comprehensibility, and adapting communication media to local cultural contexts are essential for improving migrant worker protection. The novelty of this study lies in integrating a two-way communication model with the socio-cultural context of East Nusa Tenggara as a basis for formulating more contextual, adaptive, and community-empowering communication strategies for migrant worker protection.